THE INFLUENCE OF SOCIODEMOGRAPHIC CHARACTERISTICS ON REPEAT VISIT INTEREST IN DENTAL TREATMENT AT SPECIALIST DENTAL CLINICS IN THE SPECIAL REGION OF JAKARTA - Daryono; Wirawan Dony Dahana; Yuary Farradia (RADJA PUBLIKA, 2025)
This study is a survey study on dental patients at a dental clinic in the Special Region of Jakarta. The purpose of this study is to determine the effect of sociodemographic characteristics (gender, age, education level, income and travel distance) on the intention to revisit. The number of respondents taken in this study was 375 respondents. The purposive sampling method was used in determining the respondents. Data analysis used validity and reliability tests, classical assumption tests, t tests, f tests and Regression Analysis tests. Based on the results of the study and data analysis using SPSS, it shows that: (1) Gender does not affect the intention to revisit, (2) Age has a negative effect on the intention to revisit, (3) Education level has a negative effect on the intention to revisit, (4) Income has a positive effect on the intention to revisit, (5) Travel distance does not affect the intention to revisit.